Smart Farming and Consumer Awareness; Measuring the Uptake of Agri-Tech in the Digital Landscape - Koswara, Asep (Journal of Agriculture, Agribusiness, Welfare, Technology, Humanity, Environment, Social, and Economy, 2025)
This research analyzes global search trends for "Smart Farming" and "Smart Agriculture" over the last five years, aiming to uncover how public interest in these digital agricultural terms has evolved. This research employed a quantitative research design by examining Google Trends data from last 5 years. The study identifies long-term growth, seasonal fluctuations, and surges in interest due to global events and technological advancements. The key findings reveal that "Smart Agriculture" has consistently outpaced "Smart Farming" in global popularity, with peak interest for Smart Agriculture reaching a score of 100 in March 2025, compared to 83 for Smart Farming in November 2024. From 2020 to 2025, the average interest for Smart Agriculture was 65, while Smart Farming averaged 50. Additionally, seasonal patterns indicated higher interest in Q1 (January–March), peaking in February 2025 for Smart Agriculture with a score of 96–100. The study also observed significant surges in interest in 2022, particularly around May, when interest in Smart Agriculture spiked to 91, likely driven by the Ukraine conflict and food security concerns. The research further highlights global geographical variations, with countries like Afghanistan, Armenia, and Belize showing strong interest in Smart Agriculture (scoring 100), while countries such as Haiti and Venezuela led the Smart Farming interest rankings. Overall, the study concludes that Smart Agriculture is becoming a global priority, significantly driven by technological and geopolitical factors, with broad implications for policy, research, and industry innovation.